(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Diabetes is a huge social cost burden and has become an obstacle to socio-economic development [5]. Diabetes is a non-communicable disease that is of top concern to the World Health Organization in its public health care strategy. When in the stage where monitoring and treatment are required, patient compliance with treatment plays an extremely important role in the progression and dangerous complications of diabetes. Objective: Describe the treatment compliance of inpatient type 2 diabetes patients and some related factors at Military Hospital 7 in 2023. Methods: Combined research design, sample size 384. Guaranteed research ethics. Results and conclusion: Elderly people aged 60 and over account for 83.3%. The rate of patients in rural areas is 43.2%, in urban areas it is 56.8%. People with high school education or less account for 68.8%. Have a 78.9% of patients adhere to medication. , 60.2% of patients comply with their lifestyle (tobacco, alcohol)., 26.3% of patients complied with blood sugar control and 82.6% of patients had regular check-ups.